Novel Insights Into the Interactions Between the Gut Microbiome, Inflammasomes, and Gasdermins During Colorectal Cancer - Privitera, Giuseppe; Rana, Nitish; Scaldaferri, Franco; Armuzzi, Alessandro; Pizarro, Theresa T. (Frontiers in Cellular and Infection Microbiology, 2022)
Colorectal cancer (CRC) is one of the most prevalent and deadly forms of cancer in Western countries. Inflammation is a well-known driver of colonic carcinogenesis; however, the role of the immune system in CRC extends beyond colitis-associated cancer. Over the last decades, numerous associations between intestinal dysbiosis and CRC have been identified, but the precise implications of microbiome alterations in the pathogenesis of CRC are largely unknown. Research, however, confirms the importance of a bidirectional crosstalk between the gut microbiome and the immune system in which inflammasomes, multiprotein complexes that can sense ‘danger signals,’ serve as a conduit between the two, by detecting microbial signals and activating innate immune responses, including the induction of microbicidal activities that can alter microbiome composition. Current evidence strongly supports an active role for this ‘inflammasome-microbiome axis’ in the initiation and development of CRC. Furthermore, the gasdermin (GSDM) family of proteins, which are downstream effectors of the inflammasome that are primarily known for their role in pyroptosis, have been recently linked to CRC pathogenesis. These findings, however, do not come without controversy, as pyroptosis is reported to exert both anti- or pro-tumorigenic functions. Furthermore, the multi-faceted interactions between GSDMs and gut microbiome, as well as their importance in CRC, have only been superficially investigated. In this review, we summarize the existing literature supporting the importance of the inflammasome-microbiota axis, as well as the activation and function of GSDMs, to gain a better understanding of CRC pathogenesis.